Maternal Hypertension-Related Genotypes and Congenital Heart Defects. (25th July 2020) - Lei, Yunping; Ludorf, Katherine L; Yu, Xiao; Benjamin, Renata H; Gu, Xue; Lin, Ying; Finnell, Richard H; Mitchell, Laura E; Musfee, Fadi I; Malik, Sadia; Canfield, Mark A; Morrison, Alanna C; et al.
Abstract: BACKGROUND: Maternal hypertension has been associated with congenital heart defect occurrence in several studies. We assessed whether maternal genotypes associated with this condition were also associated with congenital heart defect occurrence. METHODS: We used data from the National Birth Defects Prevention Study to identify non-Hispanic white (NHW) and Hispanic women with (cases) and without (controls) a pregnancy in which a select simple, isolated heart defect was present between 1999 and 2011. We genotyped 29 hypertension-related single nucleotide polymorphisms (SNPs). We conducted logistic regression analyses separately by race/ethnicity to assess the relationship between the presence of any congenital heart defect and each SNP and an overall blood pressure genetic risk score (GRS). All analyses were then repeated to assess 4 separate congenital heart defect subtypes. RESULTS: Four hypertension-related variants were associated with congenital heart defects among NHW women ( N = 1, 568 with affected pregnancies). For example, 1 intronic variant in ARHGAP2, rs633185, was associated with conotruncal defects (odds ratio [OR]: 1.3, 95% confidence interval [CI]: 1.1–1.6). Additionally, 2 variants were associated with congenital heart defects among Hispanic women ( N = 489 with affected pregnancies). The GRS had a significant association with septal defects (OR: 2.1, 95% CI: 1.2–3.5) among NHW women. CONCLUSIONS: We replicated a previously reported association between rs633185 and conotruncal defects. Although additional hypertension-related SNPs were also associated with congenital heart defects, more work is needed to better understand the relationship between genetic risk for maternal hypertension and congenital heart defects occurrence.